2015
DOI: 10.1016/j.neuroscience.2014.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Self administration of oxycodone alters synaptic plasticity gene expression in the hippocampus differentially in male adolescent and adult mice

Abstract: Abuse and addiction to prescription opioids such as oxycodone (a short-acting Mu opioid receptor (MOP-r) agonist) in adolescence is a pressing public health issue. We have previously shown differences in oxycodone self-administration behaviors between adolescent and adult C57BL/6J mice and expression of striatal neurotransmitter receptor genes, in areas involved in reward. In this study, we aimed to determine whether oxycodone self-administration differentially affects genes regulating synaptic plasticity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…This is consistent with differential adaptations in the expression of specific genes in adolescent versus adult mice that had self-administered oxycodone (Mayer-Blackwell et al, 2014; Zhang et al, 2014, 2015). Studies in adult mice have shown that the magnitude of antinociceptive tolerance is directly related to the level exposure to chronic MOP-r agonists (Kumar et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is consistent with differential adaptations in the expression of specific genes in adolescent versus adult mice that had self-administered oxycodone (Mayer-Blackwell et al, 2014; Zhang et al, 2014, 2015). Studies in adult mice have shown that the magnitude of antinociceptive tolerance is directly related to the level exposure to chronic MOP-r agonists (Kumar et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
“…Of note, our CPP and antinociception measurements occurred after a 14-day drug free period, considerably longer than most studies of MOP-r agonist tolerance, to allow for the transition from adolescence to adulthood. We speculate that changes in synaptic plasticity in pathways that are involved in pain and reward may occur in the mice that had self administered oxycodone in adolescent more than in the adult mice (Zhang et al, 2014; 2015, Dong et al, 2007). We cannot exclude that the differential profile observed between adult and adolescent exposure to oxycodone herein are due in part to pharmacokinetic differences across these age periods.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, OXY has reinforcing effects as measured by self-administration and condition place preference studies in rodents (Beardsley et al, 2004; Zhang Y. et al, 2009; Rutten et al, 2011; Bryant et al, 2014; Zhang et al, 2015). The mesocorticolimbic dopaminergic system is a key pathway involved in drug reinforcement (Koob, 1992) and as such, we anticipated OXY would affect activity in this neural circuit.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 61 genes that were downregulated and 18 genes that were upregulated in several brain regions in male adult and adolescent mice. Those studies focused on genes involved in neurotransmission or synaptic plasticity (Mayer-Blackwell et al 2014; Zhang et al 2015; Zhang et al 2014). …”
Section: Introductionmentioning
confidence: 99%